2018
DOI: 10.2147/ott.s154207
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic expression differences between right-sided and left-sided colon cancer based on bioinformatics analysis

Abstract: IntroductionMore and more findings have demonstrated that right-sided colon cancers (RCC) and left-sided colon cancers (LCC) are distinct clinical and biological entities and suggest that they should be treated as different diseases. However, the reasons why RCC and LCC harbor different clinical and biological features remain unclear.Materials and methodsTo identify the genomic expression differences between RCC and LCC and uncover the mechanisms underlying these differences, we chose the gene expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Various studies have provided evidence of remarkable molecular diversities between right-sided and left-sided colon cancer. Thus, an initial study by Yamauchi et al provided evidence that the frequency of CIMP-high, MSI-high and BRAF mutations gradually increased from rectum to ascending colon; in contrast, the frequency of KRAS mutations remained relatively stable at various tumor sites [ 97 , 234 ]. Sincrope et al confirmed a higher frequency of BRAF -mutated tumors among proximal colon cancers and also showed that mutation in KRAS codon 12 was more frequent in normal tumors, while non-mutated BRAF/KRAS was increased in distal tumors [ 235 ].…”
Section: Somatic Genetic Abnormalities In Colon Cancermentioning
confidence: 99%
“…Various studies have provided evidence of remarkable molecular diversities between right-sided and left-sided colon cancer. Thus, an initial study by Yamauchi et al provided evidence that the frequency of CIMP-high, MSI-high and BRAF mutations gradually increased from rectum to ascending colon; in contrast, the frequency of KRAS mutations remained relatively stable at various tumor sites [ 97 , 234 ]. Sincrope et al confirmed a higher frequency of BRAF -mutated tumors among proximal colon cancers and also showed that mutation in KRAS codon 12 was more frequent in normal tumors, while non-mutated BRAF/KRAS was increased in distal tumors [ 235 ].…”
Section: Somatic Genetic Abnormalities In Colon Cancermentioning
confidence: 99%
“…During tumor metastasis, epithelial mesenchymal transmission (EMT) is considered a vital process during which epithelial cells lose cellular polarity and cell-cell adhesion, and are transformed into separable and aggressive mesenchymal cells. 3 EMT is controlled by numerous growth factors and dissimilar factors, including Wnt, TGF-β, Notch and tyrosine kinase receptor. 4 The activation and initiation of these signaling pathways result in transcriptional suppression of numerous target genes which are involved in the loss functional activity of E-cadherin, which is a renowned marker of EMT.…”
Section: Introductionmentioning
confidence: 99%
“…MUC12 and PRAC1 were similarly downregulated in both men and women when comparing RCCs to LCCs. Recent studies have examined mRNA expression using data from TCGA and GEO comparing patients with RCC to LCC have revealed similar changes to HOXC6, PRAC1 and MUC12 (Hu et al, 2018; Peng et al, 2018). The PRAC1 gene is associated with hypermethylation, and reported to be expressed in the prostate, rectum and left-sided colon.…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis, for example, evaluates high-dimensional data at the level of gene sets, and provides a large-scale comparison at the molecular pathway and disease process level instead of examining individual genes (Subramanian et al, 2005). In a recent paper, an enrichment analyses of gene expression correlation between RCC and LCC patients was carried out using the GSE14333 dataset from the public database National Center for Biotechnology Information Gene Expression Omnibus (GEO) (Peng et al, 2018). The study revealed molecular pathways that were differentially correlated with tumor development in these two regions of the colon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation